2009
DOI: 10.1029/2008jc005104
|View full text |Cite
|
Sign up to set email alerts
|

Beaufort Gyre freshwater reservoir: State and variability from observations

Abstract: [1] We investigate basin-scale mechanisms regulating anomalies in freshwater content (FWC) in the Beaufort Gyre (BG) of the Arctic Ocean using historical observations and data collected in [2003][2004][2005][2006][2007]. Specifically, the mean annual cycle and interannual and decadal FWC variability are explored. The major cause of the large FWC in the BG is the process of Ekman pumping (EP) due to the Arctic High anticyclonic circulation centered in the BG. The mean seasonal cycle of liquid FWC is a result of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
603
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 425 publications
(641 citation statements)
references
References 59 publications
(89 reference statements)
36
603
0
2
Order By: Relevance
“…Analogously, satellite altimetry with a polar orbit (e.g., Cryosat-2, or formerly ICESat) may be used to identify changes in the circulation that is dominated by barotropic motion. In those locations where the ocean circulation is predominantly barotropic through all time scales (i.e., the Chukchi, East Siberian, and Laptev Seas), a longer record of GRACE would be fundamental to study the trend in SSH as reported by Proshutinsky et al (2009) using available tide gauges. The sparseness of the tide gauge data in space and time has made this trend difficult to investigate in the past.…”
Section: Discussionmentioning
confidence: 99%
“…Analogously, satellite altimetry with a polar orbit (e.g., Cryosat-2, or formerly ICESat) may be used to identify changes in the circulation that is dominated by barotropic motion. In those locations where the ocean circulation is predominantly barotropic through all time scales (i.e., the Chukchi, East Siberian, and Laptev Seas), a longer record of GRACE would be fundamental to study the trend in SSH as reported by Proshutinsky et al (2009) using available tide gauges. The sparseness of the tide gauge data in space and time has made this trend difficult to investigate in the past.…”
Section: Discussionmentioning
confidence: 99%
“…The most Pacific Water was found in 1998 and none in 2004 and 2005. This has been linked to temporary changes in the pathways of Pacific Water (Falck et al, 2005) and the strength of the Beaufort Gyre (Proshutinsky et al, 2009). As fractions of net sea ice melt were largely negative in all sections, this water mass in the outflow from the Arctic was most strongly influenced by brine from ice formation.…”
Section: Liquid Freshwater Components In the Western Fram Straitmentioning
confidence: 99%
“…Further studies of individual liquid freshwater components include the link of low FPW transports after 1998 and changes in the extent and the pathways of PW in the Arctic basins; in particular, a climate model simulation has shown that the pathways of PW exports from the Arctic are strongly related to the strength of the Beaufort Gyre (Jahn et al, 2010). Proshutinsky et al (2009) (2007) further suggest variability of the occurrence of PW in the Transpolar Drift on timescales of two or more years, shorter than the variability in the large-scale atmospheric circulation as represented by the Arctic Oscillation index (e.g. Thompson and Wallace, 1998).…”
Section: Changes In the Arctic Ocean Basinsmentioning
confidence: 99%
“…Field observations and results of a 1-D boundary layer model for developing near-surface temperature maxima in the Western Arctic Proshutinsky et al, 2009;Yamamoto-Kawai et al, 2009). This freshening decreases the thickness of the surface mixed layer as turbulent length scales decrease under the effects of stabilizing buoyancy fluxes (McPhee, 1994).…”
Section: Research Articlementioning
confidence: 99%
“…Therefore, a variable depth control volume was used based on the 1022 kg m -3 isopycnal near the base of the surface mixed layer (magenta line on Figure 4b). To calculate surface freshwater input, we used the freshwater content equation (Rudels et al, 2004;Proshutinsky et al, 2009) [ ]…”
Section: Nstm Heat Content and Upper Ocean Freshwater Storagementioning
confidence: 99%